2021
DOI: 10.3389/fbioe.2021.632440
|View full text |Cite
|
Sign up to set email alerts
|

miR-103a-3p and miR-22-5p Are Reliable Reference Genes in Extracellular Vesicles From Cartilage, Adipose Tissue, and Bone Marrow Cells

Abstract: Cartilage cells (CCs), adipose tissue (ASC)- and bone marrow (BMSC)-derived mesenchymal stromal cells (MSCs) have been shown as promising candidates for the treatment of osteoarthritis (OA). Despite their adaptive ability, exposure to chronic catabolic and inflammatory processes can limit their survival and healing potential. An attractive cell-free alternative or complementary strategy is represented by their secreted extracellular vesicles (EVs), having homeostatic properties on OA chondrocytes and synovial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 86 publications
0
14
0
Order By: Relevance
“…Donors, ASCs passage, culturing conditions (except OA-SF treatment) and technical platforms for ELISA and qRT-PCR were identical to those used in this study. For miRNA comparison, miR-16-5p/23a-3p/103a-3p/22-5p/26a-5p/29a-5p were selected as reference genes according to previous publications from our group [ 34 , 35 , 36 , 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…Donors, ASCs passage, culturing conditions (except OA-SF treatment) and technical platforms for ELISA and qRT-PCR were identical to those used in this study. For miRNA comparison, miR-16-5p/23a-3p/103a-3p/22-5p/26a-5p/29a-5p were selected as reference genes according to previous publications from our group [ 34 , 35 , 36 , 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…Chen et al reported miR-25-3p as the most stable miRNA in serum samples from osteoporotic rats, monkeys and women, and with osteoblast and osteoclast differentiation ( Chen et al, 2016 ). Additionally, miRs-103a-3p and − 22-5p have been reported to be highly stable in extracellular vesicles released from cartilage cells, subcutaneous adipose tissue and BMSCs of osteoarthritic patients and miR-191-5p is shown to have high stability in human bone marrow stromal cell lines and primary cells ( Costé & Rouleux-Bonnin, 2020 ; Ragni et al, 2021 ). The results of each of these studies are unique and different from our results due to differences in methodologies, and the disease states and conditions being tested.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al reported miR-25-3p as the most stable miRNA in serum samples from osteoporotic rats, monkeys and women, and with osteoblast and osteoclast differentiation (Chen et al, 2016). Additionally, miRs-103a-3p and -22-5p have been reported to be highly stable in extracellular vesicles released from cartilage cells, subcutaneous adipose tissue and BMSCs of osteoarthritic patients and miR-191-5p is shown to have high stability in human bone marrow stromal cell lines and primary cells (Costé & Rouleux-Bonnin, 2020; Ragni et al, 2021). The results of each of these studies are unique and different from our results due to differences in methodologies, and the disease states and conditions being tested.…”
Section: Discussionmentioning
confidence: 99%